Study of the influence of sustainable transport on traffic incidents - Činčikaitė, Renata; Meidutė-Kavaliauskienė, Ieva (Business, Management and Economics Engineering, 2023)
Purpose – to determine whether changes in sustainable transport influence the difference in the number of road accidents. Research methodology – synthesis and comparative scientific analysis of concepts and methods published in the literature, secondary data analysis, statistical processing, correlation-regression analysis, ARIMA method. Findings – the number of traffic accidents will increase in the coming years. According to the result of the correlation regression analysis, the number of traffic accidents is influenced by the reduced level of work capacity, people and the average traffic intensity, car/day; the change in the number of electric cars was not identified as an influencing factor. Research limitations – lack of data (incomplete statistics on sustainable vehicles) or difficult access to them. Practical implications – the results can be used in preparing strategic city plans to predict the consequences of sustainable transport regarding traffic accidents. Originality/Value – the article covers the development and changes in road traffic accidents in the big cities of Lithuania and predicts the possible reasons for this.